Occurrence in Korea of Rust Disease on Tilia mandshurica Caused by Pucciniastrum tiliae - Jae Sung Lee; Ji Hyun Park; Young Joon Choi; Hyeon Dong Shin (한국균학회지, 2023)
Tilia mandshurica trees with rust symptoms have consistently been noticed during disease surveys in Korea since 2006. Based on the morphological examination and molecular sequence analysis of the internal transcribed spacer and large subunit of ribosomal DNA, Pucciniastrum tiliae was identified as the causal fungus of rust disease. This is the first report of P. tiliae infection on T. mandshurica in Korea.